Evolution of BRET Biosensors from Live Cell to Tissue-Scale In vivo Imaging - DE, ABHIJIT; Jasani, Akshi; Arora, Rohit; Gambhir, Sanjiv S. (Frontiers in Endocrinology, 2013)
Development of bioluminescence resonance energy transfer [BRET] based genetic sensors for sensing biological functions such as protein-protein interactions [PPIs] in vivo has a special value in measuring such dynamic events at their native environment. Since its inception in the late nineties, BRET related research has gained significant momentum in terms of adding versatility to the assay format and wider applicability where it has been suitably used. Beyond the scope of quantitative measurement of PPIs and protein dimerization, molecular imaging applications based on BRET assays have broadened its scope for screening pharmacologically important compounds by in vivo imaging as well. In this mini-review we focus on an in-depth analysis of engineered BRET systems developed and their successful application to cell-based assays as well as in vivo noninvasive imaging in live subjects.